HUBUNGAN MANAJEMEN KONFLIK DENGAN KEPUASAN KERJA PERAWAT PELAKSANA DI RUANG RAWAT INAP RSU AL FATAH KOTA AMBON - Dewi Arwini Bugis; Marlinda Olivia Ressel; Nelma Likliwatil; Cosalina M Sangaji (STIKES Pasapua Ambon, 2022)
Introduction: Conflict management includes a process-oriented strategy that directs the forms of communica- tion (including behavior) from actors and outsiders and how they influence interests and interpretations. For outsiders (outside those in conflict) as third parties, what they need is accurate information about the conflict situation. This is because effective communication between actors can occur if there is trust in the third party. Method: This study uses a descriptive correlation method with a cross-sectional approach, namely by collecting data at one time (Notoadmodjo, 2010). This method is used to determine the relationship between conflict man- agement and job satisfaction of nurses at Al Fatah Hospital in Ambon. Results: most conflict management is not good with job satisfaction unsatisfied with the number of respondents 18 (40.0%) respondents while the smallest conflict management is good with job satisfaction satisfied with the number of respondents 12 (60.0%). Based on the Chi-Square test results obtained value p = 0.000 < alpha (α) 0.05 so that Ho is rejected, thus it can be said that there is a relationship between conflict management and job satisfaction of nurses at Al Fatah Hospital in Ambon. Suggestion: For hospital institutions to be able to facilitate nurses to develop knowledge related to conflict and conflict management by providing education and training through special seminars so that they can improve the conflict management abilities of nurses.